Indonesia’s Water Diplomacy and Leadership in Achieving SDG 6: A Strategic Approach to Sustainable Development - Chotimah, Amelinda Qusnul; Holland, Irene (International Journal of Science and Society, 2025)
Indonesia has contributed significantly in the effort to achieve Sustainable Development Goal 6 (SDG 6) through domestic water management and by advocating for global water diplomacy. At the domestic level, Indonesia created programs such as PAMSIMAS and the 100-0-100, which have expanded access to clean water and sanitation. However, some challenges persist, such as regional gaps, water pollution, and climate change weaknesses. At the global level, Indonesia influences platforms like the UN Water Conference and ASEAN to support fair water management and sustainable solutions. The appointment of Indonesia’s former foreign minister, Retno Marsudi, as the UN Special Envoy for Water Issues will provide Indonesia with more opportunities to impact the issue of global water regime, as this will connect international agendas with Indonesia’s national priorities. This study will explore Indonesia's dual approach opportunities to support domestic reforms with global commitments. This will be conducted through emphasizing accomplishments and challenges, as well as strengthening its role as a leader in sustainable development.